Formation of Polymeric Nanocubes by Self‐Assembly and Crystallization of Dithiolane‐Containing Triblock Copolymers. Issue 51 (24th November 2017) - Margulis, Katherine; Zhang, Xiangyi; Joubert, Lydia‐Marie; Bruening, Karsten; Tassone, Christopher J.; Zare, Richard N.; Waymouth, Robert M.
Abstract: Template‐free fabrication of non‐spherical polymeric nanoparticles is desirable for various applications, but has had limited success owing to thermodynamic favorability of sphere formation. Herein we present a simple way to prepare cubic nanoparticles of block copolymers by self‐assembly from aqueous solutions at room temperature. Nanocubes with edges of 40–200 nm are formed spontaneously on different surfaces upon water evaporation from micellar solutions of triblock copolymers containing a central poly(ethylene oxide) block and terminal trimethylene carbonate/dithiolane blocks. These polymers self‐assemble into 28±5 nm micelles in water. Upon drying, micelle aggregation and a kinetically controlled crystallization of central blocks evidently induce solid cubic particle formation. An approach for preserving the structures of these cubes in water by thiol‐ or photo‐induced crosslinking was developed. The ability to solubilize a model hydrophobic drug, curcumin, was also explored. Abstract : Polymers cubed : Cubic polymeric nanoparticles are prepared simply by self‐assembly from aqueous solutions at room temperature. Cubes with edges of 40–200 nm are formed spontaneously upon drying from micellar solutions of triblock copolymers containing a central poly(ethylene oxide) block and terminal trimethylene carbonate/dithiolane blocks. An approach for preserving the cube structure by dithiolane crosslinking is developed.